Nodo De Innovación Agrícola Y Transformador Social (2022)
The investigation focused on the south west of the country, Department of Huila, Municipality of Tello; place where there are great needs in terms of education, especially in the lack of technical training equipment, and innovation centers, being a relegated area in matters of economic growth, even when the productive capacity of the primary sector is of important representation for the Department; This, added to its great variety of thermal floors, allows offering little-explored strategies that open up the possibility of benefiting, without a doubt, its inhabitants and the entire surrounding region. Taking this into account, the studies in the present draft were analyzed at the level of urban scales, (Macro) - Department of Huila, (Meso) - Municipality of Tello, (Micro) - Urban Area of Tello, identifying their problem and solution from a productive articulation with a focus on innovation and architecture in order to create a technical training center that gives added value to the first links of the agricultural production chains.